“Low Complexity Fast Image Encryption Algorithm on Block Cipher” (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
In this paper deals with encryption using an algorithm that is efficient in case of low complexity. The idea for proposing the algorithm is to provide more securely and efficiently. Proposed algorithm for low complexity image encryption algorithm with the help of block cipher